EFEKTIFITAS KEWENANGAN PAMINAL DALAM PENEGAKAN DISIPLIN DI POLRESTA BOGOR KOTA BERDASARKAN PERKAP NO. 13 TAHUN 2016 TENTANG PENGAMANAN INTERNAL DI LINGKUNGAN KEPOLISIAN - Raden Imamul Umam Al-Mutaqin; Ani Yumarni; Inayatullah Hasyim (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
Police often accused of protecting its members who violate the code of conduct, this is caused by the severity of the punishment, giving rise to a negative outlook on society. Paminal as one among the elements in the body the police had a role in helping the enforcement of the code of conduct of the police. It is caused by the presence of police members who violate the code of conduct in the field. The method used in this research is the method of juridical sociological (empirical), namely the law as a symptom of society, as a social institution or patterned behavior. This approach is known as empirical legal research or sociological research, which is used to find out about the Enforcement Authority Paminal In Bogor Police Discipline in the city.